Mechanisms of lithium action on generation of membrane potential oscillations of the Nitella cell - Radenovic, C.N.; Maksimov, G.V.; Grodzinskij, D.M. (Физиология растений и генетика, 2015)
The results on variable mechanisms of lithium action on generation of membrane potential (MP) oscillations in the Nitella cell are presented. Generating of several classes of oscillations, single and local impulses of the membrane potential depend strongly on the high lithium concentration in the nutrient solution (LiCl concentration 10 mM), when the cell membrane is strongly excited. The assertion is that oscillations of the MP are caused by the total oscillatory transport processes for Li.⁺, K.⁺, Na.⁺ and Cl⁻ in cell membrane. The hypothesis on mechanisms of oscillatory transport processes of ions (Li.⁺, Na.⁺, K.⁺ and Cl⁻) expressed over different classes of oscillations, single and local impulses of the membrane potential across the excitable membrane of the Nitella cell is proposed. Изложены результаты исследования воздействия лития на осцилляции мембранного потенциала (МП) в клетках нителлы. Показано, что под влиянием высокой концентрации хлорида лития (10 мМ) возникает несколько классов осцилляций МП, включая единичные и локальные импульсы в случае сильного возбуждения клетки. Предполагается, что осцилляции МП, индуцируемые литием, обусловлены колебательным характером процессов транспорта Li.⁺, K.⁺, Na.⁺, Cl⁻ через клеточную мембрану. Предложена гипотеза, объясняющая механизмы колебательных процессов транспорта ионов (Li.⁺, Na.⁺, K.⁺ и Cl⁻) и наличие различных классов колебаний, а также возникновения единичных и локальных импульсов МП в возбудимой мембране клетки Nitella. Викладено результати дослідження дії літію на осциляції мембранного потенціалу (10 мМ) виникає кілька класів осциляцій МП, включно з поодинокими й локальними імпульсами в разі сильного збудження клітини. Припускається, що осциляції МП, індуковані літієм, зумовлені коливальним характером процесів транспорту Li.⁺, K.⁺, Na.⁺ і Cl⁻ через клітинну мембрану. Запропоновано гіпотезу, що пояснює механізми коливальних процесів транспорту іонів (Li.⁺, K.⁺, Na.⁺, Cl⁻) і наявність різних класів коливань, а також виникнення одиничних і локальних імпульсів МП у збудливій мембрані клітини Nitella.